The effects of spiritual intelligence and its dimensions on organizational citizenship behaviour - Anwar, Md. Aftab; Osman-Gani, AAhad M. (Omnia Science, 2015)
Purpose: Organizational citizenship behaviour may exist among employees who have inner feelings of having better work experiences by using their spiritual experiences, and also to nurture these by creating meaningful ethical work environments. These phenomena have not been sufficiently studied especially in the context of recent corporate scandals and ethical violations. For this reason, this study seeks to enrich the understanding of relationship of spiritual intelligence and its sub constructs on employee citizenship behaviour among the employees who are working in manufacturing and service organization in Malaysia.